Sectoral debt capacity and business cycles: Developing Asia and the world economy - Bada Han; Rashad Ahmed; Yothin Jinjarak; Joshua Aizenman (Asian Development Bank (ADB), 2023)
This paper reviews the patterns of sectoral debts and growth and the mechanisms explaining the adverse effects of debt burdens on growth rates. The empirical analysis covers a sample of 55 emerging and frontier market economies. Future economic growth is more sensitive to rising household debt than corporate debt. However, these effects are highly heterogenous across economies and depend on relative income. For the developing economies with a gross domestic product per capita in 2010 below 10,000 (purchasing power parity-adjusted in 2017 international dollar), the coefficients of all types of sectoral debts are negative and significant at least at the 5% level. For developing economies at higher income levels, household debts matter more than other sectoral debts for subsequent economic growth.
Keywords: E44; F34; G51; H63; 330; household debts; corporate debts; public debts; financial stability; credit cycles